PENGARUH DIMENSI FRAUD DIAMOND TERHADAP PERILAKU KECURANGAN AKADEMIK (STUDI EMPIRIS PADA MAHASISWA MAGISTER AKUNTANSI UNIVERSITAS BRAWIJAYA) - Isnan Murdiansyah; Made Sudarma; Nurkholis - (Universitas Negeri Malang, 2017)
This study aims to examine factors that influence students’ academic cheating behavior by using dimensions of fraud diamond which consists of pressure, opportunity, rationalization and capability. This study was conducted at the postgraduate (master) accounting program at the Faculty of Economics andBusiness, University of Brawijaya, Malang. The study used a combination of research methods (Concurrent Embedded Design) by using quantitative and qualitative methods, both in the collection of data and analysis, then compared the data obtained and found which data can be combined and distinguished. The results of this study provide empirical evidence that pressure, opportunity and rationalization have positive effect on student’s academic fraud behavior. It also found that the individual capability have negative effect on student’s academic fraud behavior.Keywords:Academic Fraud behavior, Fraud Diamond, Opportunity, Rationalization, Capability